2020
DOI: 10.1002/hyp.13717
|View full text |Cite
|
Sign up to set email alerts
|

Effect of anisotropy on solute transport in degraded fen peat soils

Abstract: Peat soils are heterogeneous, anisotropic porous media. Compared to mineral soils, there is still limited understanding of physical and solute transport properties of fen peat soils. In this study, we aimed to explore the effect of soil anisotropy on solute transport in degraded fen peat. Undisturbed soil cores, taken in vertical and horizontal direction, were collected from one drained and one restored fen peatland both in a comparable state of soil degradation. Saturated hydraulic conductivity (K s ) and che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 73 publications
0
11
0
Order By: Relevance
“…For the beach/dune sands, though, the aquifer sand K s value of the reference scenario (1.73 m d −1 ) was used as the minimum value. Anisotropy of K s has been reported repeatedly in peat (Beckwith et al, 2003;Wang et al, 2020), with fen peats showing a higher K s either in vertical or horizontal direction depending on peat type (Liu et al, 2016). Wang et al (2020) reported anisotropy in two fens with K s in the vertical direction being larger than the horizontal direction (K sv > K sh ) by a factor of six.…”
Section: Soil Physical Propertiesmentioning
confidence: 81%
See 2 more Smart Citations
“…For the beach/dune sands, though, the aquifer sand K s value of the reference scenario (1.73 m d −1 ) was used as the minimum value. Anisotropy of K s has been reported repeatedly in peat (Beckwith et al, 2003;Wang et al, 2020), with fen peats showing a higher K s either in vertical or horizontal direction depending on peat type (Liu et al, 2016). Wang et al (2020) reported anisotropy in two fens with K s in the vertical direction being larger than the horizontal direction (K sv > K sh ) by a factor of six.…”
Section: Soil Physical Propertiesmentioning
confidence: 81%
“…Anisotropy of K s has been reported repeatedly in peat (Beckwith et al, 2003;Wang et al, 2020), with fen peats showing a higher K s either in vertical or horizontal direction depending on peat type (Liu et al, 2016). Wang et al (2020) reported anisotropy in two fens with K s in the vertical direction being larger than the horizontal direction (K sv > K sh ) by a factor of six. Liu et al (2016) described anisotropy with the higher flow in the horizontal direction by factors of up to seven.…”
Section: Soil Physical Propertiesmentioning
confidence: 81%
See 1 more Smart Citation
“…In recent decades, human activities have caused a large area of groundwater pollution. Understanding the movement of pollutants in groundwater is a prerequisite for controlling groundwater pollution 1 , 2 . However, the groundwater seepage characteristics of different aquifer media are extremely different.…”
Section: Introductionmentioning
confidence: 99%
“…However, such changes might promote internal release of P due to favoured reduction of redox-sensitive iron(III)-P binding forms (Zak et al, 2018). On the other hand, the P transport to surface or ground water can be diminished due to lowered preferential flow, but this is a topic that requires further research (Wang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%